L’immagine linguistica del passato in base all’aspetto verbale in italiano, polacco ed inglese - Paliczuk, Aleksandra (Neophilologica, 2018)
This paper is an attempt to present different ways of conceptualizing the past in languages: Polish, Italian and English, based on the analysis of the role of the verbal aspect in the creation of the linguistic picture of the past actions in these three languages. However, the notion of verbal aspect appears in the grammars of all three analyzed languages, the same contexts are not always represented linguistically by the same verb form regarding the aspect. In this work we try to find the differences in conceiving the past seen from different perspectives, thus creating different pictures of the world.